Design Of E-Document System With Digital Signature Using User Centered Design Method - Afrianto, Irawan; Heryandi, Andri; Finadhita, Alif; Atin, Sufa (Sekolah Tinggi Teknologi Adisutjipto, 2019)
UCD (User Centered Design) is a design philosophy that places the user at the center of a system development process. The UCD approach has been supported by various techniques, methods, tools, procedures and processes that help design interactive systems that are more user-centered. This study aims to apply UCD in the design of e-document systems with digital signatures to determine user requirements for system functionality and interfaces. To find out the extent of the application of the UCD, a measurement of the level of acceptance and support of prospective users is used by making a data collection instrument in the form of a questionnaire according to the usability testing framework by using a Likert scale to calculate the variables. The results of testing of potential users showed that 85% stated that the functionality and interface design of the e-document system with digital signatures and can be developed in the next stage.